JIHAD AND RADICALISM: EPISTEMOLOGY OF ISLAMIC EDUCATION AT PESANTREN AL-FURQAN IN MUSI RAWAS DISTRICT - Idi Warsah (Universitas Islam Negeri Ar-Raniry, 2021)
Jihad and radicalism are often juxtaposed as if jihad is identical to radicalism. Unfortunately, the general public often mistakenly associates Pesantren with radicalism. Islam does not teach radicalism; instead Islam is a religion of peace. The concept of jihad in Islam cannot be identified with religious radicalism because jihad has broad meanings. This study was conducted to find out the epistemology of Islamic education at Pesantren in terms of the issues of jihad and radicalism. This study was conducted at Pesantren Al-Furqon in Musi Rawas district. Pesantren Al-Furqon organized an integrated Islamic school providing education making Islam a basis and guideline in carrying out learning activities and in shaping students’ attitudes and behavior. This study revealed that Islamic education at Pesantren Al-Furqon taught students to behave nobly according to Islamic teachings. Jihad was interpreted as sincere efforts to bring about peace but not in the sense of radicalism.